Intracameral bevacizumab administered for non-small cell lung cancer metastasis to iris - Jonathan C. Schell; Steven B. Koenig; Kenneth Bastin; William J. Wirostko (Clinics and Practice, 2011)
Ocular iris metastasis from lung cancer is uncommon. We report a patient with metastatic non-small cell lung cancer who was found to have a metastatic lesion to the iris. Local therapy for pain control and vision loss was administered with intracameral bevacizumab. Complete resolution of pain, improvement in vision, and near complete resolution of iris tumor were seen within two months. No ocular toxicity to anterior segment structures was detectable on corneal pachymetry and corneal specular microscopy. This is the first case report demonstrating safety and efficacy of intracameral bevacizumab for iris metastasis from non-small cell lung cancer.